Automatic Flood Barrier Monitoring System using Programmable Logic Controller - Ferhat, Zuhair; Md Mustam, Saizalmursidi (Evolution in Electrical and Electronic Engineering, 2023)
Every year, there are so many regions across the world face flood problems. The severity of the flood can destroy the area around the house and the destruction caused many flood victims homeless. Flood barriers exemplify the automation of flood control solutions for the sake of quick but efficient response. Thus, the flood barrier based on a Programmable Logic Controller (PLC) was proposed in this project. With the capabilities of self-activating and self-closing floodgates, these flood barriers can rise automatically with the rising flood waters keeping some regions less affected by the flood. Three different water levels are set to 1 cm, 2.5 cm, and 4 cm for the prototype and the angle for the DC motor to rotate respectively. There is also a monitoring system that can be observed in real-time and activated remotely by pressing a button using a cell phone. Water pump act as removal of water from inside the house yard to the outside of the house.